Pengaruh Pendidikan Kesehatan Penanggulangan Bencana Tanah Longsor Terhadap Kesiapsiagaan Siswa di SDN 1 Selo Boyolali - Triana Wahyuningsih; Akbar Amin Abdullah; Rizal Fajri (Inovasi Kesehatan Global, 2024)
Landslide disasters can cause environmental damage, property loss, and cause deaths, disappearances, injuries, and displacement with various health problems in refugee camps such as infectious diseases and nutritional disorders. The level of disaster risk is determined by the student's potential and preparedness which can be known from the student's interpretation of landslide disaster management. Health education is a learning process that can change students' preparedness to be able to prepare action plans to reduce the impact of landslides. The aim of this research is to determine the effect of health education on landslide disaster management at SDN 1 Selo Boyolali. This type of research uses pre-experimental methods with a quantitative approach and a one group pretest-posttest research design. The sample consisted of 29 respondents using purposive sampling technique. Measuring student preparedness uses a preparedness questionnaire sheet with 25 questions using a Likert scale. The data analysis technique uses the Wilcoxon test with the research results showing a p-value of 0.000 (p<0.05), so that it can be concluded that there is an influence of landslide disaster management health education on student preparedness at SDN 1 Selo Boyolali.